ARTIFICIAL INTELLIGENCE AS A TECHNOLOGICAL BASIS OF THE DEVELOPMENT OF BANKS - A. Berdyshev (Вестник университета, 2018)
In the face of new challenges progressive banks began to accumulate huge amounts of information about customer behavior. Thanks to the development of machine learning, artificial intelligence and cognitive computing, banks can more quickly process huge amounts of information, build more accurate models that can anticipate the needs of customers, create personalized offers and automate their services. The article defines the features of artificial intelligence technologies, the possibilities of their use and the impact on the transformation in the banking sector.